Pengembangan Sistem Informasi Administrasi Bimbingan dan Konseling Berbasis Website Di Smpit Darul Fikri Makassar - Hatimah, Husnul (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2024)
This research developed a media information system for guidance and counseling administration at SMPIT Darul Fikri Makassar. The purpose of this study was to determine; (1) Description of the needs of web-based guidance and counseling information systems at SMPIT Darul Fikri Makassar, (2) Prototype of web-based guidance and counseling information systems at SMPIT Darul Fikri Makassar, (3) Validity of web-based guidance and counseling information systems at SMPIT Darul Fikri Makassar, (4) Practicality of web-based guidance and counseling administration applications at SMPIT Darul Fikri Makassar. This research uses the Research and Development (R&D) method. The results showed that the website-based guidance and counseling administration information system media and guidebook developed were valid and practical for use in managing guidance and counseling data at SMPIT Darul Fikri Makassar, the validity and practicality of two experts in the initial product trial showed a good response with a high score and the results of the responses of counseling teachers and other users in the small group trial illustrated a positive response with high results. This shows that this guidance and counseling administration information system media is accepted and can be used as an administrative media for counseling teachers.